UFL1, a UFMylation E3 ligase, plays a crucial role in multiple cellular stress responses - Jiang, Qiang; Wang, Yongsheng; Xiang, Minghui; Hua, Jiamin; Zhou, Tianci; Chen, Fanghui; Lv, Xiaoyang; Huang, Jinming; Cai, Yafei (Frontiers in Endocrinology, 2023)
The UFM1 conjugation system(UFMylation)is a novel type of ubiquitin-like system that plays an indispensable role in maintaining cell homeostasis under various cellular stress. Similar to ubiquitination, UFMylation consists of a three-step enzymatic reaction with E1-like enzymes ubiquitin-like modifier activating enzyme5 (UBA5), E2-like enzymes ubiquitin-fold modifier-conjugating enzyme 1(UFC1), and E3-like ligase UFM1-specific ligase 1 (UFL1). As the only identified E3 ligase, UFL1 is responsible for specific binding and modification of the substrates to mediate numerous hormone signaling pathways and endocrine regulation under different physiological or pathological stress, such as ER stress, genotoxic stress, oncogenic stress, and inflammation. Further elucidation of the UFL1 working mechanism in multiple cellular stress responses is essential for revealing the disease pathogenesis and providing novel potential therapeutic targets. In this short review, we summarize the recent advances in novel UFL1 functions and shed light on the potential challenges ahead, thus hopefully providing a better understanding of UFMylation-mediated cellular stress.